A High-Resolution Interactive Atlas of the Human Brainstem Using Magnetic Resonance Histology. (16th November 2020) - Adil, Syed M; Calabrese, Evan; Charalambous, Lefko T; Cook, James; Rahimpour, Shervin; Atik, Ahmet Fatih; Cofer, Gary; Parente, Beth; Johnson, Allan G; Lad, Nandan P; White, Leonard
Abstract: INTRODUCTION: Traditional atlases of the human brainstem are limited by the inflexible, sparsely-sampled, two-dimensional nature of histology or the low spatial resolution of magnetic resonance imaging (MRI). Magnetic resonance histology (MRH) uses postmortem high-resolution MRI to circumvent the challenges associated with both modalities. METHODS: A human brainstem specimen extending from the rostral diencephalon through the caudal medulla was removed from a 65-year-old male within 24 hours of death. The specimen was formalin-fixed for two weeks, then rehydrated and placed in a custom-made MRI compatible tube and immersed in buffered liquid fluorocarbon. MRI was performed in a 7-Tesla machine with 120 unique diffusion directions. Acquisition time for anatomic and diffusion images were 14 hours and 208 hours, respectively. Segmentation was performed manually. Deterministic fiber tractography was done using strategically chosen regions of interest and avoidance, with manual editing using expert knowledge of human neuroanatomy. RESULTS: Anatomic and diffusion images were rendered with isotropic resolutions of 50 μm and 200 μm, respectively. Spatial resolution was high enough to visualize individual fasciculi of the descending corticospinal tracts intercalated between the transverse pontocerebellar fibers. Ninety different structures were segmented and 11 different fiber bundles were rendered with tractography. Angular resolution was high enough to visualize crossing fibers, such as those of the superior cerebellar peduncle. Both gray and white matter can be visualized in 3D simultaneously, such as the subthalamic nuclei and corticospinal tracts, as may be used in deep brain stimulation. CONCLUSION: We used MRH to enable unprecedented resolution in digital imaging of the human brainstem and adjacent diencephalic structures, and we then performed comprehensive segmentation and tractography to render an interactive, three-dimensional atlas of both gray and white matter. This atlas has immediate applications in neuroanatomical study and education, with the potential for future neurosurgical applications in enhancing neurosurgical planning through "safe" zones of entry into the human brainstem. We are currently building the computer infrastructure to make this atlas publicly-available.